PENGARUH KONSENTRASI OZON DAN WAKTU PAPARAN SINAR UV TERHADAP PENURUNAN KADAR COD AIR LIMBAH RS PKU MUHAMMADIYAH SURAKARTA - Siti Aisyiyah; Haryanto Haryanto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
One of the biggest contributors to liquid waste comes from hospital waste. Indonesia is estimated to produce hospital solid waste of 376,089 tons/day and 48,985.70 tons/day liquid waste production. Hospital liquid waste is one of the causes of environmental pollution. One of the parameters in wastewater is COD (chemical oxygen demand). The purpose of this study was to determine the effect of ozone concentration and exposure time to UV rays on the reduction of cod levels in wastewater. The high value of chemical oxygen demand (COD) should be treated chemically. One of them is by way of oxidation. One of the relatively new treatment systems developed in recent years is a sewage treatment system utilizing ozone gas (O3) and UV light. The research was conducted by injecting ozone and UV light into 1 liter of wastewater. Variations in the length of time exposure to UV rays in this test (2; 5; 10 15; 20) minutes and variations in ozone concentration in this test (0; 6; 1200; 1800; 2800) mg/liter. In addition, the highest COD level effectiveness was 51,11% with a COD level of 45,52 mg/L. Based on these results, this method is quite effective in reducing COD levels in PKU Muhammadiyah Surakarta Hospital.